PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP RETURN SAHAM PADA PERUSAHAAN BUMN YANG TERDAFTAR DI INDEKS LQ45 PERIODE 2014 - 2017 - Fahmi Fahmi; Kosasih Kosasih; R. Aditya Kristamtomo Putra (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
This research aims to know and explain the influence of profitability and leverage on stock returns on government-owned corporation listed in LQ45 index period of 2014-2017. Variables that are used in this research are ROE and DER towards stock returns. The populations in this study is government-owned corporation listed in lq45 index. Which samples in this study of 8 corporation with 4 period. Purposive sampling method is used as the method of sampling. The analysis method of this reearch is Multiple Regression Analysis by using eviews 9 software. The result of this research indicates that profitability and leverage significantly influence both simultaneously and partially on stock returns.